Aspirin vs. P2Y12 Inhibitor Rivalry: Which One Can be Continued During Gastrointestinal Bleeding - Muhammad Begawan Bestari; Ignatius R Joewono (Acta Medica Indonesiana, 2019)
Dual antiplatelet therapy (DAPT) is the mainstay of secondary prevention treatment for acute coronary syndrome (ACS) and ischemic stroke, especially after coronary intervention. DAPT consists of aspirin and P2Y12 receptor inhibitor (e.g. clopidogrel), and the use of DAPT has been increased over time. The most serious and common adverse effect is gastrointestinal bleeding. Guidelines in managing such condition are available among Gastroenterologist Societies and Cardiologist Societies. Most guidelines are consistent with each other to continue the use of aspirin while withholding P2Y12. However, European Society of Cardiologist (ESC) guideline in 2017 recommends P2Y12 receptor inhibitor as the preferred antiplatelet for patient with upper gastrointestinal bleeding. This review will look on the guidelines and other supporting evidence for the justification on the antiplatelet of choice.